LIMIT LOAD SOLUTIONS FOR PLATES WITH SEMI-ELLIPTICAL SURFACE CRACK UNDER BENDING AND BIAXIAL FORCES - CHEN Qiong; LV YuanJun; GAO ZengLiang (Jixie qiangdu)
As a main input of structural integrity assessment, limit load solutions of defective components are always the focus of attention. At present, limit load solutions for plates with semi-elliptical surface crack under multiaxial loading are an important research direction. Aiming at a plate with semi-elliptical surface crack under combined force and bending applied at the end sections of plate and stress applied at side surfaces of plate, limit load solutions are derived based on Von Mises yield criterion. The effect of stress applied at side surfaces can be known by yield curves shown in coordinate figure of n1. The solutions in this paper are the same as existing solutions for uniaxial load combined force and bending. At the same time, the solutions have been compared with the solutions for plates with rectangular surface crack under the same load conditions. The results show that rectangular surface crack instead of semi-elliptical surface crack will lead to overly conservative results when crack depth is larger along the thickness direction or crack length is larger along the width direction.